Unleashing QuillBot: Enhancing EFL Lexical Collocation and Writing Style in Indonesian Learners - Daulay, Sholihatul Hamidah; Astria, Maya; Azmita, Sharmila; Aulia, Sirrul (Yayasan Insan Cipta Medan, 2026)
This study aims to explore the perceptions of Indonesian EFL students toward the use of QuillBot in improving lexical collocation in writing style. The researcher uses a qualitative case study approach with questionnaires and interviews as data collection. The questionnaire was distributed to 27 students through Google Forms, and several students were interviewed by WhatsApp for deeper insight. The results showed most students gave positive responses toward using QuillBot in their writing. They agreed that QuillBot helped them correct the grammatical errors, improve choices, and enhance writing clarity and fluency. It also increased their writing independence, vocabulary use, and confidence in writing use. Overall the findings indicate that QuillBot is not only a useful digital tool for improving writing quality but also an effective learning aid that supports students’ self-learning and writing development in EFL contexts.